The Study Of Socio-Psychological Problem Of Loneliness - et. al., Fakhriddin Yuldashev, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The problem of loneliness belongs to the object of study of sciences the expression of human development, such as sociology, philosophy, psychology, culturology, pedagogy, medicine and theology. Each of them analyzes the phenomenon of loneliness, proceeding from the research framework of his own science, and tries to enrich himself with a new-a new concepted aspect. Alternatively, it should be noted that the theoretical and practical development of this problem acquires relevance within the framework of Social Psychology, since the phenomenon of loneliness is directly related to the interpersonal relationship between people. The study of the concept of “socio-psychological loneliness” indicates the importance of fully revealing the meaning and essence of the term “loneliness”. This article is dedicated to the problem of loneliness. It reveals the etymology of the concepts of loneliness, solitude and alienation. The results of the survey are also analyzed.